Alterações no equilíbrio ácido-base em equinos submetidos à prova de três tambores ou à competição de enduro de 160 Km - Brito, Helena Cristina Delgado [UNESP] (2014)
The aim of the present study was to determine physiological, electrolytic and hemogasometric parameters of Quarter horses, with distinct fitness levels, submitted to a simulated barrel racing (BR). Moreover, the alterations in the acid-base balance were compared between Quarter and Arabian horses, competitors of equine endurance of 160 km. Besides, it was performed a comparison of two methods to determine the variable Atot. In the experiment 1, 10 Quarter horses were distributed in two groups, one composed by high fitness animals (HF, n=5) and other with lower fitness (LF, n=5). These horses were submitted to a BR and it was verified the possible alterations in the acid-base balance using the traditional and mechanistic approaches, being the collecting moments before and after the exercise. In the experiment 2, 16 Arabian horses participated in an endurance ride of 160 km and they were evaluated before, during and after the competition. Samples of venous blood were collected in both experiments. The heart frequency was determined only for the Quarter horses. Physiological, electrolytic and hemogasometric parameters were quantified for all equines of the present study. Were performed for the experiment 1, the t-paired and not-paired t-test between moments and groups, respectively. For the experiment 2, it was performed the analysis of variance (ANOVA) to compare the variables followed by Tukey’s test. All analysis were performed with 95% of significance. The FCpeak e FCm were 206 ± 8,7 and 203 ± 12,9 bpm for the HF group, and 181 ± 7,5 e 177 ± 3,5 bpm for the LF group. The main disturbance found by the two approaches for the BR was the metabolic acidosis. For this discipline, total matching between the approaches was obtained. For endurance, 10 animals sucessfully completed the competition and 6 were eliminated. The main disturbance found in the sucessfull animals for both approaches was the metabolic alkalosis. In the ...